The effect of normothermic recirculation before cold preservation on post-transplant injury of ischemically damaged donor kidneys. - Moers, C; van Rijt, G; Ploeg, R; Leuvenink, H (2012)
Kidneys recovered from donation after cardiac death (DCD) are increasingly used to enlarge the deceased donor pool. Such renal grafts, especially those derived from uncontrolled DCD, have inevitably sustained profound warm ischemic injury, which compromises post-transplant function. Normothermic recirculation (NR) of the deceased donor's body before organ cooling could be an interesting approach to mitigate the detrimental effect of warm ischemia. To date, however, there is no evidence coming from preclinical studies to support the principle of NR in kidney transplantation. In this study, we subjected 48 Lewis rat kidneys to 15 or 30 min of warm ischemia, and subsequently 0, 1, or 2 h of NR. After 24 h cold storage, kidneys were transplanted into a recipient animal and 24 h later we measured the percentage of cortical necrosis, and determined gene expression of heme oxigenase-1, heat shock protein-70, transforming growth factor-β, kidney injury molecule-1, interleukin-6, hypoxia inducible factor-1α, monocyte chemoattractant protein-1, and α-smooth muscle actin in kidney tissue. We found that NR had no significant influence on any of these markers. Therefore, we conclude that this animal study by no means supports the presumed beneficial effect of NR on kidneys that have been severely damaged by warm ischemia.